Is the C34T polymorphism of the AMPD1 gene associated with athlete performance in rowing? - Cieszczyk, P.; Eider, J.; Ostanek, M.; Leonska-Duniec, A.; Ficek, K.; Kotarska, K.; Girdauskas, G. (International Journal of Sports Medicine, 2011)
The skeletal muscle-specific isoform of adenosine monophosphate deaminase (AMPD) is one of the most important regulators of muscle energy metabolism. A nonsense C to T transition in nucleotide 34 (C34T) in exon 2 of AMPD1 gene converts the codon CAA into the premature stop-codon TAA. 127 Polish male rowers including Olympic and world champions were recruited for this study. Controls samples were obtained from 251 unrelated volunteers. Statistically significant differences in genotype distribution were observed when only a whole group of rowers (88.19% CC, 11.81% CT, 0% TT; p=0.009) were compared with controls (75.31% CC, 23.10% CT, 1,59% TT). A significant deficiency of the T allele compared to control samples was noted in the elite rowers (4.55%, p=0.021) and non-elite rowers (6.63%, p=0.023), whereas this trend was even stronger when compared with the controls for the whole group of rowers (5.91%, p=0.002). Our results suggest that the T allele is associated with physical performance level, therefore, it may be included in the group of performance altering polymorphisms as a negative factor to athletic performance.